An Immunocytochemical Profile of the Endocrine Pancreas Using an Occlusive Duct Ligation Model - Page, Benedict J; du Toit, Don F; Muller, Christo JF; Mattysen, Johannes; Lyners, Romeo (JOP. Journal of the Pancreas, 2016)
Context Ligation of the pancreatic duct, distally to its confluence into the bile duct has been shown to induce endocrine tissue regeneration. The surplus endocrine tissue formed is presumed to be able to replace pathologically and/or experimentally compromised tissue. Objective This is a quantitative study on the histology of duct ligated pancreas employing immunocytochemistry and computerised morphometry. Interventions Pancreatic duct ligation was performed on 25 groups of six normal Sprague-Dawley rats. Experimental animals were sacrificed at 12-hour intervals from day one to ten post-duct ligation and every 24 hours thereafter to day 14, the pancreas removed, fixed and processed. Six consecutive 3-6 micron serial sections were cut on a rotary hand microtome, floated onto 3-aminopropyl-trimethoxysilan coated slides and alternatively immunocytochemically stained for insulin, glucagon, pancreatic polypeptide and somatostatin. Results Pancreas transformation between days ½ and 3½ was characterised by acinar deletion and the appearance of immunoreactive cells for the primary endocrine hormones. Transdifferentiation of existing endocrine tissue saw islet insulin core cells replaced by pancreatic polypeptide- and somatostatin positive cells, glucagon deletion and random appearance of all endocrine cell types within the inter-islet interstitium by day 3½. Days 4 to 14 were characterised by cellular migration and islet reconstruction. Conclusions To date our laboratory has investigated transplantation of foetal tissue beneath the renal capsule in syngeneic, isogeneic and allogeneic normal and diabetic rats. As pancreatic duct ligation induces the development of surplus endocrine tissue our next step would be to investigate the use of ligated pancreas as a replacement for foetal tissue. Image: Arrangement of bile and pancreatic ducts in the laboratory rat.